2000
DOI: 10.2166/wst.2000.0277
|View full text |Cite
|
Sign up to set email alerts
|

Removal and recovery of heavy metals by bacteria isolated from activated sludge treating industrial effluents and municipal wastewater

Abstract: A total of nineteen metal-resistant and non-resistant bacteria from activated sludge treating both metal-contaminated industrial effluents and municipal wastewater were isolated and identified. These included both Gram-positive (e.g. Micrococcus) and Gram-negative (e.g. Pseudomonas) bacteria. The biosorption capacity of these strains for five different heavy metals (copper, nickel, zinc, lead and chromium) was determined at pH 5 and initial metal concentration 100 mg/L. Pseudomonas pseudoalcaligenes and Microc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(79 citation statements)
references
References 8 publications
6
66
0
1
Order By: Relevance
“…Low removal of nickel at lower pH range by Pencillium chrysogenum has also been reported (Tian-Wei et al 2004). Removal of copper and lead (Leung et al 2000) and chromium and nickel (Congeevaram et al 2007) by Micrococcus luteus also followed the same trend. Very few bacterial species are known to remove metals at pH above 8.…”
Section: Determination Of Mic Optimal Temperature and Phsupporting
confidence: 57%
“…Low removal of nickel at lower pH range by Pencillium chrysogenum has also been reported (Tian-Wei et al 2004). Removal of copper and lead (Leung et al 2000) and chromium and nickel (Congeevaram et al 2007) by Micrococcus luteus also followed the same trend. Very few bacterial species are known to remove metals at pH above 8.…”
Section: Determination Of Mic Optimal Temperature and Phsupporting
confidence: 57%
“…Low removal of nickel at lower pH range by Pencillium chrysogenum has also been reported [46]. Removal of copper and lead by Micrococcus luteus [47] also showed the same trend. And the reason behind this results is that the percentage removal of chromium at high pH is depends upon the negative charge present on the fungal surface [48] due to the functional groups which helpful in the binding of cation Cr (VI) up to the optimum range of pH while at lower pH, due to the protonation of binding site resulting from high concentration of proton, negative charge intensity on the site is reduced which results in the reduction or inhibition for the binding of metal ion.…”
Section: Effect Of Ph and Temprature Variationssupporting
confidence: 54%
“…In similar studies with other metal cations, Malekzadeh et al (11) isolated a strain of Pseudomonas sp. highly capable of accumulating uranium at pH 6.5; also, Leung et al (10) found that lead and copper uptake by P. pseudoalcaligenes and Micrococcus luteus increases as pH values raise from 2 to 6.…”
mentioning
confidence: 95%